Pengaruh Media Sosial Marketing Melaui Aplikasi TikTok Terhadap Keputusan Pembelian Pada Shopee - Fu'adah, Anisa Samrotul (International Journal Administration, Business & Organization, 2023)
The purpose of this research is to find out and analyze how social media marketing can influence or not influence online purchase decisions made by shopee consumers to students in the city of Bandung. Data collection was obtained by distributing questionnaires online via the Google Form link to 120 respondents. The data analysis technique used in this study is simple linear regression analysis. The results of this study indicate that social media marketing has a positive and significant effect on purchasing decisions. Social media marketing contributes 60.2% to purchasing decisions, while 39.8% is influenced by other variables.